Effects of magnesium sulfate on apoptosis in cultured human gastric epithelial cells. Issue 2 (3rd March 2016) - Xia, Yuan; Bo, Agula; Liu, Zhiyue; Chi, Baofeng; Su, Zhuang; Hu, Yueling; Luo, Ru; Su, Xiong; Sun, Juan
ABSTRACT: This study investigated the effect of magnesium sulfate (MgSO4 ) on the viability of the human gastric adenocarcinoma (AGS) epithelial cell line. AGS cells were exposed to various concentrations of MgSO4 for different time-periods and the effects on cell viability, DNA fragmentation, apoptotic gene expression, and caspase activity were investigated. A range of tests were employed in this study, including a lactate dehydrogenase cell viability assay, annexin V staining, reverse transcription polymerase chain reaction (RT-PCR), terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL), and several caspase activity assays. Expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), Fas ligand (FasL) and Fas receptor (FasR) were analyzed using RT-PCR. These analyses revealed that MgSO4 induced a dose-dependent reduction in AGS cell viability. Annexin V staining did not differ between negative control and treated cells, indicating that no apoptotic cells were detected. The TUNEL assay data were consistent with the annexin V staining results. FasL mRNA expression was increased and FasR mRNA expression was decreased in a dose-dependent manner by MgSO4 . MgSO4 treatment tended to cause an initial (1 h) dose-dependent increase in the activities of caspase-3, -6, -8, and -9; however, these activities were subsequently inhibited (24 h). We deduced that MgSO4 exerted an anti-apoptotic effect in AGS cells via caspase activation.